Cytotoxic Sesquiterpenoids from the Stem Bark of Aglaia harmsiana (Meliaceae) - Hersa Milawati; Winda Sukmawati; Desi Harneti; Rani Maharani; Nurlelasari Nurlelasari; Ace Tatang Hidayat; Darwati Darwati; Unang Supratman; Yoshihito Shiono (Indonesian Journal of Chemistry, 2020)
Three aromadendrane-type sesquiterpenoids, spathulenol (1), 4β,10α-dihydroxyaromadendrane (2), and 4α,10α-dihydroxyaromadendrane (3) were isolated from the stem bark of Aglaia harmsiana (Meliaceae). Compound 3 was isolated for the first time from Aglaia genus. The chemical structures of isolated compounds were elucidated by various spectroscopic methods, including one and two-dimensional NMR, as well as mass spectroscopy analysis. These sesquiterpenoids 1-3 were evaluated for their cytotoxic activity against MCF-7 breast cancer cell lines. The IC50 value of compound 1-3 were 31.65 ± 0.1, 8.41 ± 0.04 and 2.80 ± 0.02 µM, respectively. Among the aromadendrane-type sesquiterpenoids, compounds 2 and 3, which do not have a double bond, showed higher activity than compound 1. Whereas, compound 3 showed the strongest activity indicate that α configuration of hydroxyl group increases the cytotoxic activity.